Competências na formação docente: uma análise do curso de Pedagogia PROFEBPAR- UFMA - CARDOSO, Luciane Menezes (2021)
This research, entitled COMPETENCES IN TEACHING EDUCATION: an analysis of the PARFOR/UFMA pedagogy course is part of the Research Line “Educational Institutions, Curriculum, Training and Teaching Work” of the Graduate Program of the Federal University of Maranhão. This work discusses the competence in the formation of teachers in the PARFOR/UFMA pedagogy course. In this sense, this study aimed to analyze the elements that constitute the pedagogical project of the course object of this investigation in its organization by competences. In this study, we adopted the qualitative research methodology with a critical approach, as we understand that reality necessarily involves dialectical criticism and is historically constructed with its multiple contradictions. This study articulated bibliographical research, supported by the studies of Pereira (1999), Tanuri (2000), Freitas (2002), Saviani (2005, 2008, 2010, 2011), Romanelli (2007), André (2010), Santos and Pereira (2016) that deal with teacher training. On curriculum, we rely on studies by Lopes (2008), Garcia (2013), Sacristán (2013, 2017), Moreira and Candau (2014), Silva (2019). With regard to competences, we sought theoretical support in Deluiz (1996, 2001), Ramos (2001), Zarifian (2001, 2003), Perrenoud (2002), Stroobants (2004), Roche (2004), among others. Regarding the documentary research, several documents were analyzed, including the Law of Guidelines and Bases of Education no 9.394/96, Decree no 6.094/2007, Decree no 6.755/2009, Resolution CNE/CP no 1/2002, Resolution No. 2/2015, among others of equal relevance. The techniques for data collection were: semi-structured interviews and an online questionnaire. The data obtained refer to the categories defined a priori, namely: Teacher education, Skills and Curriculum, in addition to other categories of analysis that emerged from the survey data. Two coordinators participated in the investigation, being a general coordinator of PARFOR and a coordinator of the PARFOR/UFMA pedagogy course, four professors, eleven graduate students of the aforementioned course at the Cururupu center, in a total of 17 subjects. Data were analyzed and organized using the discursive textual analysis technique, based on Moraes and Galiazzi (2016). By addressing the historical background, we situate initial teacher education in Brazil that is articulated with society's demands for education, we also discuss the 1990s reforms and the reordering of curriculum policies, including for teacher education from the LDBEN 9,394/96. Then, we deal with PARFOR and the competency-based curriculum, analyzing its creation as a public policy for teacher education, explaining its operationalization at the national level and its implementation at UFMA, especially in the pedagogy course. The investigation found that the theoretical conception that underlies the course curriculum is from a critical perspective and understands education as a political act at the service of social transformation. In addition, the course aims to develop in students-teachers skills and abilities to master, integrate and mobilize knowledge in theoretical, technical and practical dimensions for satisfactory performance in the various fields of activity of the pedagogue. We hope that this study will contribute to strengthening the training of basic education teachers, as well as improving PARFOR's actions at local and national level.